PENGARUH TEKTONIK DAN IKLIM TERHADAP PERUBAHAN LINGKUNGAN ENDAPAN KUARTER DAERAH SUMPUR, SUMATERA BARAT - Mulyana, Herman; M.Lumbanbatu, Ungkap; Moechtar, Herman (Pusat Survei Geologi, 2008)
Based on the depositional environment, the Quaternary deposits in the study area can be divided into five groups, i.e : (a) fluvial-channel deposits, (b) floodplain deposits (c) lake deposits, (d) transition/ tidal deposits, and (e) swamp deposits. Furthermore, this Quaternary deposits represent 3 (three) depositional intervals, namely Depositional Interval I-III.The development of the Quaternary environment and changes of basin fill in the research area were influenced by tectonic and climatic changes. Changes in climatological conditions, from the humid-subhumid into dry, probably due to global climatic changes following the Milankovitch cycles. While the vertical and lateral changes of environment systems could be influenced by reactivation of Singkarak-Solok fault segment. Keywords: Quaternary, tectonic, climate, environment